Unusual Presentation of Tuberculous Thyroid Abscess in a Background of Hashimoto’s Thyroiditis in a Chronic Hepatitis B Carrier - Sakthivel Chinnakkulam Kandhasamy; Sunil Kumar; Anubhav Sangwan; Neelam Sahani; Gopalakrishnan Gunasekaran; Sunil Kumar Meena; Swapnil Singh Kushwaha (Case Reports in Surgery)
Tuberculosis of thyroid gland is a very rare disease. It has variable presentations and may be sometimes associated with autoimmune thyroiditis. We report a case of 45-year-old male, with left sided painless neck swelling, with a purulent discharging sinus over it associated with night sweats and loss of appetite. Thyroid imaging disclosed heterogeneous enhancement of left lobe of thyroid gland with internal vascularity and coarse calcifications. Core needle biopsy revealed caseous necrosis and AFB positivity. Patient had thyroid peroxidase antibody and thyroglobulin antibody positivity and the rest of thyroid function tests were normal. Patient had positive Mantoux test, hepatitis B surface Ag, and low viral DNA. The patient was diagnosed as being a case of tuberculous abscess of thyroid gland and was put on antitubercular therapy for 2 months. Patient subsequently underwent left hemithyroidectomy when there was no response. Histopathological examination revealed tuberculosis of thyroid gland. A final diagnosis of tuberculous abscess of thyroid gland in a background of Hashimoto’s thyroiditis in a chronic HBV carrier was made. Therefore, although rare tuberculosis of thyroid should be kept in mind as a differential diagnosis of thyroid swelling.